Caviar and fish roe substitutes: Current status of their nutritive value, bio-chemical diversity, authenticity and quality control methods with future perspectives. (April 2021) - Farag, Mohamed A.; Abib, Bishoy; Tawfik, Sherouk; Shafik, Noha; Khattab, Amira R.
Abstract: Background: Caviar, salt-cured unfertilized roe of sturgeon fish, is a food delicacy associated with royalty and nutritive properties since prehistoric times. The drastic decline in wild sturgeon populations has led to an increased aquaculture production of caviar roe and its substitutes from other species i.e. lumpfish, herring, tobiko, cod, shad and mullet. Fish roes are highly nutritive foods comprising a myriad of biochemical components with several health benefits viz. high quality protein, polyunsaturated fats, vitamins and minerals which are influenced by its biodiversity, fish farming and industrial processing. Scope and approach: We provided in this review extensive knowledge regarding interspecies compositional variability among roe produced by different fish species, with respect to the impact of fish farming, different processing methods and storage conditions on caviar/roe quality. Different quality control methods viz. biochemical, analytical and molecular methods, for evaluating caviar authenticity and biodiversity of roe products are summarized as essential tools to assess roe counterfeiting and/or mislabeling. Key findings and conclusions: Biochemical markers for discriminating the roe origin (wild vs. domesticated fish) are highlighted with lipid profiles being more efficient than protein analysis. Molecular genetic techniques were also posed as competent species-discriminatory tools. Other underexploited tools were introduced as future perspectives viz. color measurements and computer vision, as rapid non-destructive methods. Intelligent packaging should be sought as a valuable method for monitoring roe freshness. The full health benefits of roe, as a promising functional food, are not yet fully capitalized upon which warrants future research to prove its efficacy using mechanistic and clinical studies. Graphical abstract: Image 1 Highlights: Chemical makeup and health benefits of caviar and its roe substitutes. Impact of fish storage and processing on caviar/roe quality are summarized. Quality control methods for assessing caviar authenticity and origin. Differentiation between wild and farmed roe is presented.